A devastating complication “white cord syndrome” following posterior cervical decompression for ossification of the posterior longitudinal ligament stenosis - Christian Permana; Yoga Arif Syah Hidayat; Fadhil; Muhammad Sinatrya Caropeboka; Mardjono Tjahjadi (Indoscholar, 2021)
Reperfusion injury of the spinal cord or “white cord syndrome” (WCS) refers to the sudden onset of neurological deterioration after spinal decompressive surgery. It is thought to be caused by reperfusion injury of the spinal cord. The risk of WCS might be increased in elderly and patients with chronic hypertension as commorbidities. A 50-year-old male suggestive a continuous ossified posterior longitudinal ligament (OPLL) with cervical spinal stenosis from C2-C4 underwent posterior decompression and posterior fixation from C2 to C4. After the patient recover from anesthesia, he developed hemiparesis on right side with motor strength 1/5. Immediate postoperative CT scan imaging revealed no malpositioned screw, on cervical MRI disclosed a hyperintense signal in T2-weighted sequences at C3-C4 levels and the diagnosis of WCS was suspected. A high dose methylprednisolone according to NASCIS II, mannitol, and methylcobalamin were given. On post-operative day (POD)-1 the patient's muscle strength improved to grade 3/5 in the upper extremity and to grade 4/5 in the lower extremity but the elbow flexion muscle strength still 1/5. Two weeks after surgery the patient able to walk normally but the upper extremity still no improvement. There are still no class I, II, and III evidence backing specific treatment of WCS. However, there are several prevention strategies to decrease the risk of WCS such as CSF pressure management, remote ischemic preconditioning (RIPC), intraoperative monitoring, and technique switch to laminoplasty. We recommend that the importance of early recognition and prompt treatment of white cord syndrome to minimize the complication.